2007
DOI: 10.1152/physiolgenomics.00082.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of deficiency in SREBP cleavage-activating protein on lipid metabolism during intermittent hypoxia

Abstract: Obstructive sleep apnea (OSA), a condition leading to intermittent hypoxia (IH) during sleep, has been associated with dyslipidemia, atherosclerosis, and increased cardiovascular mortality. We previously showed in C57BL/6J mice that IH causes hypercholesterolemia and upregulation of sterol regulatory element binding protein (SREBP)-1, a transcription factor of lipid biosynthesis in the liver. The goal of the present study was to provide mechanistic evidence that IH causes hypercholesterolemia via the SREBP-1 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 63 publications
(94 reference statements)
4
43
0
Order By: Relevance
“…Why does acute hypoxia decrease VLDL secretion while chronic IH apparently augments it (39)? Perhaps the chronicity of hypoxia or intervening periods of normoxic recovery provides an opportunity for transcriptional upregulation of genes involved in lipid synthesis and secretion (38). Normoxic mice in the previous study were also food restricted (39) to match the CO2 was collected at 10-min intervals for 1 h to assess relative rates of whole body ␤-oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Why does acute hypoxia decrease VLDL secretion while chronic IH apparently augments it (39)? Perhaps the chronicity of hypoxia or intervening periods of normoxic recovery provides an opportunity for transcriptional upregulation of genes involved in lipid synthesis and secretion (38). Normoxic mice in the previous study were also food restricted (39) to match the CO2 was collected at 10-min intervals for 1 h to assess relative rates of whole body ␤-oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the hypothalamic-pituitaryadrenal axis increased serum cortisol levels 28) , leading to hyperglycemia and insulin resistance 29) . Lastly, an experimental study has shown that intermittent hypoxia caused an increase in hepatic levels of triglyceride and phospholipid, and upregulated the expression of genes involved in lipid biosynthesis in mice 30) . Therefore, nocturnal intermittent hypoxia may increase serum triglyceride levels.…”
Section: Discussionmentioning
confidence: 99%
“…Being overweight may also be associated with metabolic risk factors indirectly, mediated by nocturnal intermittent hypoxia. For example, reduced oxygen saturation enhances sympathetic activity to raise blood pressure 23) and the production of VLDL in liver, and raises blood triglyceride levels 30) , common pathways in overweight individuals. Therefore, being overweight may weaken the effect of nocturnal intermittent hypoxia on high blood pressure and high triglyceride levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, the direct relationship between sleep apnoea or intermittent hypoxia and its cardiovascular consequences is not fully elucidated. We and others have evidence of a role for haemodynamic alterations [5], inflammation [6] and metabolic dysregulations [10,11]. OSA is also frequently associated with obesity, which is the main confounder for detrimental consequences of OSA [12].…”
Section: Introductionmentioning
confidence: 95%